PERAN ORANG TUA DALAM BIMBINGAN BELAJAR ANAK PADA MASA PANDEMI COVID-19 DI KABUPATEN MANGGARAI, NTT - Yovita Hamun; Frans Laka Lazar; Fabianus Hadiman Bosco (Program Studi Guru Sekolah Dasar (UNIKA Santu Paulus Ruteng), 2021)
Many parents have been thought that guiding children to study is the teacher's job at school and not theirs, and aslo they are busier to work outside the house, they do not have time to be with their children at home. They provide various facilities and financial support to children but no moral support is provided. There is an imbalance between the role of parents and children's learning success. The purpose of this study is to describe the role of parents in the guidance of children at SDK St. Maria Ruteng III. The method used in this study is descriptive qualitative where the researcher makes structured interviews to 12 respondents. The results showed that parents at SDK St. Maria Ruteng III carries out several roles in guiding their children during the pandemic covid-19, including managing time and providing children's learning places, providing children's learning facilities, paying special attention to children who have learning difficulties, paying attention to activities that support children's learning and controlling activities that interfere with children's learning, giving reward for children who succeed in achieving achievements and punishment for children who violate the rules together, and provide support or motivation to children to improve achievement or learning outcomes